Adsorption of Gold from Thiosulfate Leaching Solutions using Polyethylenimine Functionalised Magnetic Nanoparticles - Ilankoon, Nirmala Damayanthi (Curtin University, 2020)
In this research polyethylenimine coated iron oxide magnetic nanoparticles (PEI-MNPs), as a novel adsorbent, was evaluated for the adsorption of gold from thiosulfate leaching solutions that contain gold, copper and calcium thiosulfate. This novel adsorbent can simply be separated from the solution using an external magnetic field, followed by gold adsorption. Gold elution from the adsorbent was simple and rapid.